2022
DOI: 10.1093/gbe/evac093
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Evolution of RNase T2 Family and Gametophytic Self-incompatibility System in Plants

Abstract: Ribonuclease (RNase) T2 genes are found widely in both eukaryotes and prokaryotes, and genes from this family have been revealed to have various functions in plants. In particular, S-RNase is known to be the female determinant in the S-RNase-based gametophytic self-incompatibility system. However, the origin and evolution of the RNase T2 gene family and gametophytic self-incompatibility system are not well understood. In this study, 785 RNase T2 genes were identified in 81 sequenced plant genomes representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Sequence analyses of the S -genes have been extensively conducted in Solanaceae and Rosaceae ( McClure 2004 ; Williams et al 2014 ; Kubo et al 2015 ; Wu et al 2020 ; Vieira et al 2021 ; Lv et al 2022 ); however, similar studies on Plantaginaceae species are still limited ( Lai et al 2002 ; Qiao et al 2004 ). Prior this work, the first S C -haplotype of cultivar A. majus , which conferred self-compatibility due to loss of S-RNase , has been reported ( Li et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analyses of the S -genes have been extensively conducted in Solanaceae and Rosaceae ( McClure 2004 ; Williams et al 2014 ; Kubo et al 2015 ; Wu et al 2020 ; Vieira et al 2021 ; Lv et al 2022 ); however, similar studies on Plantaginaceae species are still limited ( Lai et al 2002 ; Qiao et al 2004 ). Prior this work, the first S C -haplotype of cultivar A. majus , which conferred self-compatibility due to loss of S-RNase , has been reported ( Li et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, the timing of origination of S-RNase is undetermined, which were given to the following two possible explanations: (1) RNase emerged as an S -gene before the diversification of eudicots, and subsequent gene loss (e.g., C. alba scaffold124) or translocation ( P. pubescens Chr03) of S-RNase occurred in many evolutionary entities, and (2) RNase have not come into tight linkage with incipient SLFs to form a functional S -locus which controlled self-incompatibility in the common ancestor of eudicots until the divergence of Plantaginaceae species. By comparing Ks values of ancient SLFs and S-RNase in Rosoideae species, Lv et al concluded that ancestral SLFs originated before the split of grape and Rosaceae ancestor and after the split, the ancestral S-RNase emerged in the Rosaceae common ancestor ( Lv et al 2022 ). Based on these results and principle of parsimony, hypothesis (1) would be the most plausible model to illustrate the origin and evolution of the S -locus supergene.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of available plant genomes provides an opportunity to resolve the evolutionary relationships of the RNase T2 gene family and the origin of S -RNase SI on a broad scale. A study based on phylogenetics, syntenic analyses, and identification of whole gene duplication (WGD) events revealed that lineage-specific WGD resulted in expansion of the RNase T2 family ( Lv et al. 2022 ).…”
Section: Origins Evolution and Breakdown Of Si Systemsmentioning
confidence: 99%
“…Loss of S -RNase GSI is caused mainly by inactivation, deletion, or duplication of S -loci rather than defects in S -RNase alone, possibly due to additional functions of S -RNase beyond its role in SI ( Zhao et al., 2022 ). Phylogenetic studies have classified T2-RNases into three clades (class I, class II, class III); all functional and predicted S -RNases are members of the class III T2-RNase clade and are found exclusively in eudicots ( Ramanauskas and Igic, 2017 ; Lv et al., 2022 ). Although there is evidence that an ancestral state of tightly linked pollen and pistil components may have existed prior to the eudicots, a genome study of pineapple ( Ananas comosus ) revealed that an RNase T2 family gene was closely linked to several F-box-associated genes ( Chen et al., 2019a ).…”
Section: Origins Evolution and Breakdown Of Si Systemsmentioning
confidence: 99%
“…Notably, GSI systems and homomorphic systems have been studied more extensively than heteromorphic systems ( McCubbin, 2008 ). Studies have reported that in Solanaceae, Rosaceae and Plantaginaceae, GSI is based on the SLF ( SFB )/ SRNase system, and in Brassicaceae SSI is based on the SP11 ( SCR )/ SRK system ( Lv et al, 2022 ; Goring et al, 2023 ). Significant advancements have been made in comprehending the molecular foundation of HetSI, particularly in Primula and Fagopyrum ( Banović et al, 2010 ; Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%